Artralgias, dores ósseas, anticorpos anti-nucleares positivos e trombocitopenia...diagnóstico: Doença de Nieman-Pick - Ambrósio, C (2009)
The differential diagnosis of rheumatic diseases is sometimes very complex given the lack of specificity of some clinical manifestations. A careful physical examination with the aid of laboratory and radiographic findings can lead us to some rare conditions, reminding that they should never be forgotten in the differential diagnosis. The authors present a case report of a woman referred to the rheumatology department with joint and bone pain. Physical examination and laboratory findings lead us to the diagnosis of type B Niemann-Pick disease. Some considerations about the diagnostic challenge of this rare clinical condition are made.